The Influence of the Principal's Leadership Style on BOS Fund Fraud with Accountability as an Intervening - Nawawi, Muhamad Sidi; Hendrian, Hendrian; Pambelum , Yohanes Juni (International Journal of Applied Management and Business, 2024)
Therefore, this research aims to determine the influence of the Principal's leadership style on fraud in School Operational Costs (BOS) funds in Indonesia with accountability as an intervening variable. Methodology/approach – The research uses descriptive statistical analysis techniques and inferential statistical analysis to analyze sample data and the results are applied to the population, with the Structural Equation Model (SEM) with a Partial Least Square (PLS) approach based on the results of theoretical studies and hypotheses to be tested as well as this approach quantitative. Findings - The results obtained from this research are that there is a significant influence of the principal's leadership style on BOS fund fraud, there is a significant influence of the principal's leadership style on accountability, there is a significant influence of accountability on BOS fund fraud, and there is a significant influence of the principal's leadership style on fraud BOS funds with accountability as an intervening variable. So far previous research has been carried out to analyze the transparency and accountability of the use of BOS funds, but no one has specifically examined the influence of the school principal's leadership style on BOS fund fraud. Therefore, in this study, we want to examine the influence of the school principal's leadership style on BOS fund fraud by including accountability, which has been the subject of previous research, as an intervening variable.